Desain Lembar Kerja Praktikum Berbasis Masalah untuk Menunjang Keterampilan Proses Sains (KPS) pada Materi Kualitas Perairan - Amizera, Susy; Destiansari, Elvira; Santri, Didi Jaya; Santoso, Lucia Maria (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Industrial activities can increase waste discharge which has an impact on reducing water quality. Decreasing water quality requires methods for solving problems. The development of problem solving abilities can be improved in practical activities. In practical learning, students are expected to be able to reconstruct concepts through solving problems, so they can develop science process skills. These practical activities can be facilitated using problem-based practical worksheets. The aim of this research is to design problem-based practicum worksheets to support students' science process skills related to preliminary studies, product development design, validity testing, and student responses to small-scale testing. The type of research used is development research using the Borg & Gall model to small scale trials. This research was carried out from July to August 2023. The data collection techniques used in this research were interviews and giving questionnaires. The instruments used in this research were an interview guide sheet, a questionnaire sheet for product validation, and a student response questionnaire sheet. Next, the data was analyzed descriptively. Based on the research results, it can be seen that the practicum worksheet that was developed began with a preliminary study regarding the need for problem-based practicum worksheets on water quality material. The design developed is based on problem-based practical worksheet components that have been validated by two experts. Furthermore, a small-scale trial was carried out which showed that the material aspects were categorized as very good, the graphics were categorized as good, and the language was categorized as very good. Thus, the results of this development can be continued in large-scale tests and can be implemented in the practical learning process.